Literary culture in Cuba : Revolution, nation-building and the book. - Kumaraswami, Par (Manchester University Press, 2017)
Based on over 100 interviews with a wide range of actors, the book breaks new ground by going beyond the conventional approach and by going beyond the canon of texts known outside Cuba. It thus presents a historical analysis of the evolution of literary culture from 1959 to the present, as well as a series of more detailed case studies (on writing workshops, the Havana Book Festival and the publishing infrastructure) which reveal how this culture is created in contemporary Cuba. It contributes a new and complex vision of revolutionary Cuban culture which is as detailed as it is comprehensive.